2006
DOI: 10.1080/13803390500212896
|View full text |Cite
|
Sign up to set email alerts
|

State Regulation in Adult ADHD: An Event-related Potential Study

Abstract: The state regulation hypothesis postulates that poor task performance of children with ADHD is related to poor energetical state control. The current study aimed to investigate whether such a deficit persists in adult ADHD. Event-related potentials (ERPs) were recorded during administration of a Go/No-Go task that incorporated the stressor presentation rate of stimuli. It was found that males with ADHD responded slower than control males in the slow condition, which was accompanied by smaller parietal P3s, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 50 publications
10
51
2
Order By: Relevance
“…Hence, quickening the pace of the task creates a raised energetic state among children with ADHD, thereby normalizing RTV. This set of results is corroborated by studies that have found that varying the ER on a trial-by-trial basis also seems to reduce ADHD-related increases in RTV [87,88]. Similar to the argument that speeding the ER increases the energetic state, a variable ER is believed to create a higher state of vigilance, thereby keeping individuals, including those individuals with ADHD "on their toes" while performing the task [89].…”
Section: Reaction Time Variability Manipulationssupporting
confidence: 70%
“…Hence, quickening the pace of the task creates a raised energetic state among children with ADHD, thereby normalizing RTV. This set of results is corroborated by studies that have found that varying the ER on a trial-by-trial basis also seems to reduce ADHD-related increases in RTV [87,88]. Similar to the argument that speeding the ER increases the energetic state, a variable ER is believed to create a higher state of vigilance, thereby keeping individuals, including those individuals with ADHD "on their toes" while performing the task [89].…”
Section: Reaction Time Variability Manipulationssupporting
confidence: 70%
“…Regular P300 amplitudes are in contrast with the data from other studies (Szuromi et al, 2011;Woltering et al, 2013). However, most studies used Go/No-Go tasks (e.g., Wiersema et al, 2006) to measure response inhibition and are therefore difficult to compare. A possible explanation for the intact P300 potentials may be a compensation of impaired early stimulus discrimination by effortful activation during later stages of processing, which has also been suggested by others for the domains of WM (Missionier et al, 2013) and selective attention (Barry et al, 2009).…”
Section: Discussioncontrasting
confidence: 59%
“…Comparably, under-arousal in the non-degraded condition and optimal levels of arousal in the degraded condition may explain why children with AD/HD reported slightly greater perceived levels of effort in the non-degraded condition and a significant drop in effort levels in the 60% condition, relative to controls. That is, children with AD/HD may have perceived less effort was required because arousal may have been at an optimal level due to the arousing qualities of the difficult degradation task (Wiersema et al, 2006a). However, it should be noted that an alternative possibility for low reported effort levels in the degraded condition by the AD/HD group is that they were not aware of their internal effort levels, which may have in fact been raised.…”
Section: Perceived and Objective Measures Of Effort And Arousalmentioning
confidence: 97%